Hubungan Psikologi, Tasawuf dan Pendidikan Agama Islam - Mutholingah, Siti; Qomarudin, A. (STAI Ma'had Aly Al-Hikam Malang, 2022)
The purpose of this study is to examine the relationship between psychology, Sufism and Islamic Education. This study uses a literature review or referred to as a literature study. The result of this study is that Islamic Education as an effort to develop the entire human element, namely physical, psychological (soul) and reason, requires other disciplines, namely psychology and Sufism as disciplines that examine the psychological (psychological) aspects of humans in depth. The findings of this study are Islamic teachings are taught in PAI which consist of an exoteric dimension (outside) and an esoteric dimension (inside), where in teaching the esoteric dimension to students, Islamic Education requires psychology and Sufism. In practice, psychology and sufism can be used as the basis for character based Islamic education development. Thus, it can be concluded that the relationship between psychology, Sufism and Islamic Education is that in the learning process PAI is very closely related to the disciplines of psychology and Sufism, especially in terms of teaching the esoteric dimension of Islamic teachings (the spirit of Islamic teachings) because this esoteric dimension can only be understood by students. the psychic (psychological) aspect of humans.